STUDI PENGARUH PEMBANGUNAN CLOSURE DIKE WADUK WONOGIRI TERHADAP KONDISI BANJIR DI HILIR WADUK - AMALIA, ADANI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Wonogiri Reservoir is a multipurpose reservoir in the upper part of Bengawan Solo. It is functionalized for irrigation water supply, hydropower and flood control at the upstream area of Bengawan Solo River Basin. The high sediment production at intake decreases the effectiveness of storage capacity for irrigation water supply purpose. The Government of the Republic of Indonesia through Balai Besar Wilayah Sungai (BBWS) Bengawan Solo has conducted a study of reducing sediment deposition at intake and constructed closure dike (dike that separate reservoir area) for sedimentation deposit of Keduang River and a new spillway for flushing sediment. The change of reservoir characteristic is followed by the change of reservoir operational for flood control. Therefore, it is necessary to study the change of reservoir operation system during flood period and learn the impact to downstream area of Wonogiri Reservoir. Study about the impact of reservoir operation rule at the downstream area has been done by using mathematic method for hydrology calculation. The calculation along Bengawan Solo River (with the upstream area is Wonogiri Reservoir and downstream area is Colo Weir) is using channel routing method. It has been 12 lateral inflows that contribute flow discharge for channel routing calculation besides reservoir outflow discharge. There are six types of reservoir outflow discharge, i.e.: existing condition (reservoir without closure dike) and new condition (reservoir with closure dike) with 3 types of return period (60 years, 500 years, and 5,500 years/PMF). The calculation is using HEC-HMS. Design floods at Colo Weir are calculated by using channel routing method at the downstream area of reservoir (for existing and new condition). The increase of 60 years, 500 years, and 5,500 years are 35%, 13%, and 67%. Despite the increase of peak discharge, the volume discharges are decreased. The percent decrease of volume discharges are 45% and 8% in 60 years and 500 years of return period. Volume discharge increase and the percent increase is 25% for PMF condition. The contribution of discharge from lateral inflow against the flood discharge at Colo Weir is shown by the ratio of volume discharge from lateral inflow and volume discharge from reservoir. The ratio of 60, 500, and 5,500 years return periods in new condition are 39.2%, 29.9%, and 17.3%. Maximum water elevation at Colo Weir can be determined from discharge-water level rating curve. The flood hydrograph of 60 years return period reaches its maximum water level at elevation of +109.72 m for existing condition and +110.21 m for new condition. The maximum elevation in new condition is reached within 5 hours earlier than the existing one. For 500 years return period, the flood hydrograph reaches its maximum at elevation of +110.61 m for existing condition (time to peak: 6th hours) and +110.82 m for new condition (time to peak: 7th hours). For PMF condition, the existing condition reaches the maximum water level at 6th hours and 52nd hours with the value of water level is +111.51 m, the new condition reaches maximum at 15th hours with the water level is +111.67 m. The conclusion is the operation rule of Wonogiri Reservoir during flood period in existing condition is more safety than the new one. Keywords: Colo Weir, channel routing, lateral inflow, HEC-HMS